PEDOMAN TATA CARA WUDHU DAN TAYAMUM DENGAN BAIK DAN BENAR MENURUT SUNNAH DI PEMBELAJARAN KEMUHAMMADIYAHAN BERBASIS ANDROID IKEST MUHAMMADIYAH PALEMBANG - Ridwan Hakim; Arif Fadillah (jurnal kesehatan terapan sains dan teknologi, 2023)
ABSTRACT Background: learning the procedures for ablution and tayammum is fundamental in islam, and correct knowledge of these procedures is a must. therefore, the development of this application will enable users, especially for them to learn in an interactive and effective way. apart from that, the use of mobile technology in religious learning can also enable a wider dissemination of religious knowledge, allowing more individuals to understand and follow the procedures for ablution and tayamum correctly. Research Method: this research uses data collection techniques using qualitative methods. namely by interviews and observations as well as a waterfall design. Results: the results of the research were to create "guidelines for procedures for ablution and tayamum correctly and correctly according to the sunnah in android-based muhammadiyah learning.". Conclusion: the conclusion of this research is that with an android-based application for ablution and tayamum procedures, this application can help students and the public learn the correct procedures for performing ablution and tayammum according to the sunnah. this application is based on android so it can make it easier and help students to learn the correct procedures for performing ablution and performing tayamum at all times.